Effect of herbal extracts on growth, physiological parameters, yield and yield attributes of Indian mustard - Manish Meena; Har Vir Singh; RS Jat; GL Yadav; MD Meena; MK Meena (Journal of Oilseed Brassica, 2026)
A field experiment was conducted during winter season of 2016-17 at ICAR-Directorate of Rapeseed and MustardResearch, Bharatpur, Rajasthan to evaluate the effect of herbal extracts on growth, physiological parameters, yield andyield attributes of Indian mustard (Brassica juncea L.). The experiment was laid out in randomized block design with fourtreatments and five replications, viz. herbal extracts, RDF + one irrigation, RDF + KNO3 spray and Control. Resultsrevealed that maximum plant height (231.2 cm), plant leaves (49.6), Leaf area index (5.9), chlorophyll content (50.8),primary (7.3) and secondary branches (20.6) had with T2 treatment receiving RDF + one irrigation. The yield and yieldattributes; length of silique (5.1 cm), number of seeds/siliqua (17.0), and test weight (5.2 g) were highest under thetreatment of RDF+one irrigation as compared to other treatments. This study indicated that application of recommendeddose of fertilizers with one irrigation at 65 days after sowing was found more beneficial in terms of getting higher yieldand plant growth in climatic conditions of Rajasthan.